2009
DOI: 10.1073/pnas.0809974106
|View full text |Cite
|
Sign up to set email alerts
|

Switching direction in electric-signal-induced cell migration by cyclic guanosine monophosphate and phosphatidylinositol signaling

Abstract: Switching between attractive and repulsive migration in cell movement in response to extracellular guidance cues has been found in various cell types and is an important cellular function for translocation during cellular and developmental processes. Here we show that the preferential direction of migration during electrotaxis in Dictyostelium cells can be reversed by genetically modulating both guanylyl cyclases (GCases) and the cyclic guanosine monophosphate (cGMP)-binding protein C (GbpC) in combination wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 37 publications
(68 reference statements)
2
87
0
Order By: Relevance
“…Similarly to chemotaxing cells, several studies have reported activation and/or localization of typical leading edge markers, including actin polymerization, phosphatidylinositol 3,4,5-trisphosphate (PIP3), and/or extracellular signal-regulated kinase (ERK) 1/2, at the front of cells undergoing either shear-flowmediated migration or electrotaxis (4)(5)(6)(7). However, these activities were observed under steady-state conditions and, because these activities are associated with random projections, their appearance at the leading edge most likely merely reflects the abundance of projections at the front induced by mechanical or electrical forces.…”
mentioning
confidence: 99%
“…Similarly to chemotaxing cells, several studies have reported activation and/or localization of typical leading edge markers, including actin polymerization, phosphatidylinositol 3,4,5-trisphosphate (PIP3), and/or extracellular signal-regulated kinase (ERK) 1/2, at the front of cells undergoing either shear-flowmediated migration or electrotaxis (4)(5)(6)(7). However, these activities were observed under steady-state conditions and, because these activities are associated with random projections, their appearance at the leading edge most likely merely reflects the abundance of projections at the front induced by mechanical or electrical forces.…”
mentioning
confidence: 99%
“…Several other pathways may also contribute to chemotaxis (9,22). We demonstrated that Dictyostelium cells also show robust electrotaxis and are a good model for dissecting the molecular/genetic basis of electrotaxis (19,29). Extracellular pH, [K ϩ ], and electroporation significantly affected V m and correspondingly reduced or abolished electrotaxis.…”
Section: Discussionmentioning
confidence: 81%
“…This probabilistic view of chemotaxis might also hold true for other modes of oriented cell movement, such as electrotaxis or thermotaxis. In electric fields, signalling molecules such as PI3K and sGC translocate to the anode or cathode side of the applied electric field and increase the probability of pseudopod formation, thereby inducing directed movement (Sato et al, 2009;Zhao et al, 2006).…”
Section: Discussionmentioning
confidence: 99%